From political opponents to enemies? The role of perceived moral distance in the animalistic dehumanization of the political outgroup. (May 2016) - Pacilli, Maria Giuseppina; Roccato, Michele; Pagliaro, Stefano; Russo, Silvia
In this paper, we analyzed the relationships among political identity, the perception of moral distance between the political ingroup and the political outgroup, and outgroup animalistic dehumanization. One correlational and one experimental study revealed a positive correlation of ingroup identification (Study 1, N = 99) and salience of ingroup membership (Study 2, N = 96) with the degree to which participants dehumanized the outgroup. This relationship was mediated by the perceived moral distance between the ingroup and the outgroup. The limitations, implications, and possible developments derived from the present findings are discussed.